Dynamical analysis of scabies delayed epidemic model with second-order global stability - Emad Fadhal; Ali Raza; Eugénio M. Rocha; Wafa F. Alfwzan; Muhammad Rafiq; Nauman Ahmed; Muhammad Bilal (PLoS ONE, 2025)
Scabies is a highly transmitted skin disease that can affect people of all ages, especially children. According to the World Health Organization (WHO), South Asia and sub-Saharan Africa are the regions most affected. For the study of the dynamics of scabies in the population, the mathematical model is designed with delay differential equations (DDEs) for four subpopulations: unvaccinated individuals, vaccinated individuals, infected individuals, and recovered individuals. The fundamental properties of the model, such as positivity, boundedness, existence, and uniqueness, are proved. The equilibria, reproduction number, sensitivity analysis, and (Local and Global) stabilities for the second order are studied rigorously. The numerical simulations were performed to confirm the validity of their theoretical results. The study’s findings suggest delay-based modeling of scabies and the advanced stability analysis provides a better understanding of epidemic management and disease dynamics over time.